Caracterização da comunidade bacteriana de filtros biológicos percoladores tratando efluente anaeróbio - Érika Ferreira de Abreu (2014)
The study characterized the bacterial community developed in trickling filters (TF) used in the post-treatment of UASB reactor effluent. The TF had similar configurations, but one was filled with plates of polyethylene and the other, interspersed plates with polyurethane sponges. The sponge-TF showed higher biomass retention and higher removal efficiency of carbonaceous organic matter and ammonium ion. Food/ microorganism relationships (g CODsoluble / g TVS.d) estimated for each reactor showed that the nutritional conditions were scarcer in sponge-TF due to the higher biomass accumulation in their compartments. Pyrosequencing analyzes showed that bacterial community developed in each reactor was completely different, even though the predominant phylum has been Proteobacteria in both reactors. In the sponge-TF, other abundant phyla were Verrucomicrobia and Planctomycetes, which include, respectively, slow-growing oligotrophic bacteria and bacteria with complex cell structure, characteristics of K-strategist organisms. However in plate-TF, the other abundant groups were Acidobacteria phylum and Clostridia class, the latter known to include generalist fast-growing bacteria, characteristics of r-strategist organisms. Within the nitrogen cycle, the predominant group was the denitrifying bacteria. The relative abundances of nitrifying were higher in TF-plate, however, in absolute terms, sponge packing media retained greater amount of bacteria because of its greater capacity for solids retention. The coexistence of nitrifying, denitrifying and anammox in sponge-TF compartments means that different metabolic pathways were involved in the removal of nitrogenous compounds. Variations in the structures of the bacterial community in general, including in the AOB and denitrifying, were attributed primarily to reductions in the concentrations of substrates (organic matter, ammonium ion, etc.) occurring along the compartments and over time. We conclude that the sponge packing media promoted greater retention of micro-organisms and diversification of environmental conditions in the TF, selecting a biomass primarily constituted of slow-growing microorganisms, more efficient in the removal of organic and nitrogen compounds, resulting in enhancement of UASB-TF system.